The effects of supplementation of probiotics, prebiotics, or synbiotics on patients with non-alcoholic fatty liver disease: A meta-analysis of randomized controlled trials - Xing, Wenmin; Gao, Wenyan; Lv, Xiaoling; Zhao, Zhenlei; Mao, Genxiang; Dong, Xiaoyan; Zhang, Zuyong (Frontiers in Nutrition, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) has become the most prevalent chronic liver disease nowdays. New studies still presented inconsistent results on the effect of probiotics, prebiotics, or synbiotics supplements. This study aims to combined analysis the effectiveness of these microbial therapies on NAFLD disease. Methods: Eligible randomized-controlled trials reporting the effect of probiotics, prebiotics, or synbiotics in NAFLD were searched in PubMed, Web of Science, Embase, Google scholar, and CNKI databases from 2020 to Jul 2022. The changes in the outcomes were analyzed using standard mean difference (SMD) and 95% confidence intervals (CIs) with a random- or fixed -effects model to examine the effect of microbial therapies. Subgroup analysis, influence and publication bias analysis were also performed. The quality of the eligible studies was evaluated using the Cochrane Risk of Bias Tool. Results: Eleven studies met the inclusion criteria involving 741 individuals. Microbial therapies could induce improvements in liver steatosis, total cholesterol (TC), triglyceride (TG), low-density lipoprotein(LDL-c), alanine aminotransferase (ALT), alkaline phosphatase(ALP), gamma-glutamyl transpeptidase (γ-GGT), and homeostasis model assessment-insulin resistance (HOMAI-R) (all P<0.05). But microbial therapies could not ameliorate body mass index (BMI), energy, carbohydrate, fat intake, fasting blood sugar, HbA1c, insulin, high-sensitivity C-reactive protein (hs-CRP), and hepatic fibrosis of patients with NAFLD. Conclusion: This combined analysis results presented evidence for the improvement of probiotics, prebiotics, or synbiotics supplementation on liver steatosis, liver enzymes, and lipid profiles in patients with NAFLD.